Size compensation in Drosophila after generalised cell death - Pinal, Noelia; Ruiz-Losada, Mireya; Azpiazu, Natalia; Morata, Ginés (Frontiers in Cell and Developmental Biology, 2023)
Regeneration is a response mechanism aimed to restore tissues that have been damaged. We are studying in the wing disc of Drosophila the regenerative response to a dose of Ionizing Radiation that kills over 35% of the cells distributed all over the disc. After such treatment the discs are able to restore normal size, indicating there is a mechanism that repairs generalised damage. We have tested the role of the JNK, JAK/STAT and Wg pathways, known to be required for regeneration after localised damage in the disc. We find that after irradiation there is size compensation in the absence of function of these pathways, indicating that they are not necessary for the compensation. Furthermore, we also find that generalised damage does not cause an increase in the proliferation rate of surviving cells. We propose that irradiated discs suffer a developmental delay and resume growth at normal rate until they reach the final stereotyped size. The delay appears to be associated with a developmental reversion, because discs undergo rejuvenation towards an earlier developmental stage. We argue that the response to generalized damage is fundamentally different from that to localized damage, which requires activity of JNK and Wg.